Security Order and Strategic Alignment in Europe and the Asia-Pacific : Times of Global Power Shifts - Atanasova, Elena; Satō, Y.; Sauer, Tom (Routledge, Taylor & Francis Group, 2025)
Elena Atanassova-Cornelis, Yoichiro Sato, Tom Sauer, and their contributors examine the implications of the shifts in power for the regional security order, as the longterm relative decline of the US standing in the global hierarchy of power is more pronounced than ever due to the challenges it faces from the rising China in Asia and the reviving Russia in Europe.The world is in disarray, and the balance of power is shifting, which results in enhanced tensions and wars, including on the territory of Europe. The complexity of the international order that prevails today possibly misleads us toward viewing everything in terms of a bipolar competition, as predicted by systemic-level realism. While membership of the multilateral NATO Alliance expands in Europe in light of the ongoing Russian invasion of Ukraine, China's assertive behavior in Asia has produced numerous strategic alignments that are short of a formal alliance involving Asian states, the US, and European countries. 'Hedging' strategies are commonly found in Asian states' approaches to security, working against the bifurcation of powers. Contrarily, European entries into alignments in the 'Indo-Pacific' have demonstrated the inseparability of security in Asia from security in Europe through the shared thread of 'engaging the US'. Whether China defines its challenge against the US in regional or global terms also has differing implications for the evolution of the international system. This book, with contributions by Asian, European, and North American experts, provides an overview of the two regions' differing alignment paths in comparative and inter-regional perspectives.The book is a valuable resource for academics, researchers, practitioners, and policy analysts interested in European and Asia-Pacific security, as well as international and regional security issues.
Keywords: National security -- Europe.; National security -- Pacific Area.; Alignment; Asia-Pacific; Europe; Power Shift; Security order; Strategy; elektronické knihy; electronic books